2014
DOI: 10.1186/1756-3305-7-280
|View full text |Cite
|
Sign up to set email alerts
|

Pyriproxyfen for mosquito control: female sterilization or horizontal transfer to oviposition substrates by Anopheles gambiae sensu stricto and Culex quinquefasciatus

Abstract: BackgroundThe use of gravid mosquitoes as vehicles to auto-disseminate larvicides was recently demonstrated for the transfer of pyriproxyfen (PPF) by container-breeding Aedes mosquitoes and presents an appealing idea to explore for other disease vectors. The success of this approach depends on the female’s behaviour, the time of exposure and the amount of PPF that can be carried by an individual. We explore the effect of PPF exposure at seven time points around blood feeding on individual Anopheles gambiae sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 64 publications
(84 reference statements)
6
72
0
1
Order By: Relevance
“…Similarly, the ability of autodissemination to transfer lethal concentrations of insecticides has been successfully demonstrated in the laboratory and the field for Ae . albopictus and other mosquito vectors [12,2529]. Previous studies, however, have used only open cups to assess autodissemination efficacy and did not examine efficacy in cryptic habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ability of autodissemination to transfer lethal concentrations of insecticides has been successfully demonstrated in the laboratory and the field for Ae . albopictus and other mosquito vectors [12,2529]. Previous studies, however, have used only open cups to assess autodissemination efficacy and did not examine efficacy in cryptic habitats.…”
Section: Discussionmentioning
confidence: 99%
“…An additional feature of PPF that may be examined in future ADAM-related work are its effects on female fertility and male spermiogenesis [23,[43][44][45]. Specifically, PPF contamination of females can reduce fertility of females and males, which can negatively impact the population in addition to the pupacidal effect of PPF [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, Koama et al showed that a single exposure to pyriproxyfen treated netting reduced the number of eggs laid by >75% over three gonotrophic cycles when the first blood-meal was shortly after exposure (Koama et al, 2015). It has been shown that pyriproxyfen is a potent inhibitor of pupal eclosion at very low concentrations and that adult mosquitoes can transfer pyriproxyfen to larval waters during oviposition (Mbare et al, 2014;Wang et al, 2014;Lwetoijera et al, 2014b). The impact of so-called autodissemination will depend on the dosage of pyriproxyfen remaining on tarsi by the time of oviposition and the volume of water in breeding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Mbare et al conducted similar trials with An. gambiae and showed that exposure up to 24 h before or after blood-feeding resulted in a moderate reduction in egg laying of between 56 and 62% (Mbare et al, 2014). Exposure to pyriproxyfen 48 h before blood-feeding had only a 32% reduction in oviposition, while exposure 48 or 72 h after blood-feeding had no impact (Mbare et al, 2014).…”
Section: Introductionmentioning
confidence: 99%